Governance of Healthcare Data: International Standards and Recommendations - Mahuntragul, Atcharee (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
In the global phenomenon, the aging population becomes a critical issue. Data and information concerning elderly citizens are increasing and are not well organized. In addition, these unstructured data and information cause the problems for decision makers. Since we live in a digital world, Information Technology is considered to be a tool in order to solve problems. Data, information, and knowledge are crucial components to facilitate success in IT service system. Therefore, it is necessary to study how to organize or to govern data from various sources related elderly citizens. The research is conducted due to the fact that there is no internationally accepted holistic framework for governance of data. The research limits the scope to study on the healthcare domain; however, the results can be applied to the other areas. The research starts with an ongoing research of Dahlberg and Nokkala (2015) as a theory. It explains the classification of existing data sources and their characteristics with the focus on managerial perspectives. Then the studies of existing frameworks at international and national level organizations have been performed to show the current frameworks, which have been used and are useful in compiling data on elderly citizens. The international organizations in this research are selected based on their reputations and the reliability to obtain information. The selected countries at national level provide different point of views between two countries. Australia is a forerunner in IT governance while Thailand is the country which the author has familiar knowledge of the current situation. Considered the discussions of frameworks at international and national organizations level illustrate the main characteristics of each framework. At international organization level gives precedence to the interoperability of exchanging data and information between different parties. Whereas at national level shows the importance of the acknowledgement of using frameworks throughout the country in order to make the frameworks to be effective. After the studies of both international and national organization levels, the thesis shows the summarized tables to answer the fitness to the proposed framework by Dahlberg and Nokkala whether the framework help to consolidate data from various sources with different formats, hierarchies, structures, velocities, and other attributes of data storages. In addition, suggestions and recommendations will be proposed for the future research.